2014
DOI: 10.1177/1045389x14529026
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional near-field multiple signal classification algorithm–based impact localization

Abstract: The susceptibility of composite materials to internal damage caused by low-velocity impact is well known and creates a major concern related to structural health monitoring. This research presents a near-field impact monitoring method based on the two-dimensional multiple signal classification method for the composite structure. Since elastic waves attenuate quickly in the complex aircraft composite structures and impacts may happen near the sensors, near-field impact monitoring method is important. However, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 39 publications
0
36
0
Order By: Relevance
“…This limitation is due to the signal model, which considers plane waves only (or far-field source). High-resolution algorithms suited for the identification of near-field sources has been developed [59,60,61], and could be used to identify the parameters of waves with a wavefront which is not plane. Moreover, uncertainties in the wavevector could be quantified by using results of the perturbation analysis of the ESPRIT algorithm [48].…”
Section: Discussionmentioning
confidence: 99%
“…This limitation is due to the signal model, which considers plane waves only (or far-field source). High-resolution algorithms suited for the identification of near-field sources has been developed [59,60,61], and could be used to identify the parameters of waves with a wavefront which is not plane. Moreover, uncertainties in the wavevector could be quantified by using results of the perturbation analysis of the ESPRIT algorithm [48].…”
Section: Discussionmentioning
confidence: 99%
“…According to the formula deduced by the authors (Zhong et al., , ; Yuan et al., ), the observed data output from PZT i of PBSA can be represented as bold-italicxi(t)=rris(t)ejω0τi+bold-italicni(t),i=1,2,...,Mwhere, τi is the arriving time difference between PZT i and PZT 0. The array steering vector a i (r,θ) for the impact signal is ai(r,θ)=rriexp(jω0τi)…”
Section: Impact Signal Model Using Pbsamentioning
confidence: 99%
“…However, most of current researches were restricted to localization impact in the far‐field of isotropic plate. To deal with the near‐field monitoring problem, the authors in previous work proposed a uniform linear sensor array (ULSA)‐based MUSIC algorithm for impact localization to solve the near‐field monitoring problem (Zhong et al., , ; Yuan et al., ). However, for the applications on the real complex structures, some challenges still exist.…”
Section: Introductionmentioning
confidence: 99%
“…The orthogonality of the two subspaces can be utilized to estimate the signal parameters. Therefore, similar to the formulas of uniform linear array deduced by the authors [10][11][12], the observed signal vector from the P-B sensor array is analyzed first in this section.…”
Section: Impact Array Signal Modelmentioning
confidence: 99%